Youth expectations in job search in Serbia - Pavlović, Dejana; Zubović, Jovan; Zdravković, Aleksandar (Industrija, 2017)
Youth on the labour market in developing countries such as Serbia, Macedonia, Bosnia and Herzegovina are facing numerous difficulties, with almost a half of their population aged between 15 -24 do not work or work in informally. The reasons may be numerous. The financial crisis and the low economic development of the country have had negative impact on young generations and this resulted in lack of sufficient jobs vacancies. In addition, the reasons for their slow entry into the labour market could be the lack of experience, low education among young people etc. Although employers have certain expectations of young people, once they enter the labour market young people have certain values that are important for them when choosing a job. The paper presents the research on the expectations of young people entering labour market in the Republic of Serbia. According to survey results based on analyses of youth’ expectations and preferences in Serbia regarding potential work conditions, authors have by the means of factor analysis identified which groups of factors are the most important for young people ages between 16 and 30 in job finding in Serbia. The results showed that there is a significance of three questions: 1. Job does not affect the private life; 2. Work resources are provided; 3. Work is safe. In the conclusion, if a company ensures that these three issues are regulated, it will more likely employ young professionals.
Keywords: Market; Labour Market; Labour; Job